HUMAN CAPITAL APPROACH TO INCREASING PRODUCTIVITY OF HUMAN RESOURCES MANAGEMENT - Sukoco, Iwan; Prameswari, Dea (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2017)
ABSTRACTThis paper discusses the human capital approach to manage human resources becoming more productive. The method used in this research is qualitative method with descriptive research. Human capital approach for the implementation has five main components, namely individual capability, individual motivation, the organization climate, workgroup effectiveness and leadership. the importance of the role of human resources in the activities of the company, then the company should manage human resources as best as possible because the key to success of a company is not only the benefits of technology and the availability of funds, but also on the human factor. Based on observations in Indonesia, there are still many companies thathave not implemented the most optimal approach to human capital. The results of the study indicate that the human capital component is not yet optimal, especially in terms of individual capability and individual motivation.Keywords : Human capital approach, individual capability, individual motivation, the organization climate, workgroup effectiveness and leadership ABSTRAKTulisan ini membahas pendekatan human capital untuk mengelola sumber daya manusia yang lebih produktif. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan jenis penelitian deskriptif. Pendekatan human capital menerapkan lima komponen utama, yaitu individual capability, individual motivation, the organization climate, workgroup effectiveness dan leadership. Menyadari pentingnya peran sumber daya manusia dalam kegiatan perusahaan, maka hendaknya perusahaan perlu mengelola sumber daya manusia sebaik mungkin karena kunci sukses suatu perusahaan bukan hanya pada keunggulan teknologi dan tersedianya dana, melainkan juga pada faktor manusianya. Berdasarkan pengamatan masih banyak perusahaan di Indonesia yang belum menerapkan pendekatan human capital secara optimal. Hasil penelitian mengindikasikan bahwa penerapan komponen human kapital belum optimal terutama pada aspek individual capability dan individual motivation.Kata kunci : Pendekatan human capital, individual capability, individual motivation, the organization climate, workgroup effectiveness and leadership